The Use of Visual Media in Educating Deaf Students on Prayer Practices - Irfani, Salistya; Suwantoro, Suwantoro (Universitas Pahlawan Tuanku Tambusai, 2025)
Learning media plays an important role in the learning process, especially for students with hearing impairments. Choosing the right media can improve understanding, attract interest, and facilitate the delivery of material. In learning to pray for deaf students, relevant media helps convey messages clearly and effectively. This study was conducted to determine how to use image media in learning prayer material for deaf students at SMPLB Asih Mulya Jungcangcang Pamekasan and to determine what are the supporting factors and inhibiting factors for the use of image media in learning prayer material for deaf students at SMPLB Asih Mulya Jungcangcang Pamekasan. This study uses qualitative research with a descriptive research type. And to support the discussion based on field facts, the researcher obtained data sources using interviews, observations, and documentation. The informants were PAI teachers, students, parents/relatives and principals. The results of the study indicate that: first, the use of image media in learning prayer material at SMPLB Asih Mulya Jungcancang Pamekasan includes planning by compiling teaching modules and choosing the right methods and media, implementation through observing, asking, trying and associating activities, and evaluation using text and non-text. Second, supporting factors include the suitability of the media to the needs of students, teacher creativity, adequate school facilities, and parental support. The inhibiting factors are the limitations of image media, the lack of mastery of sign language by Islamic Religious Education teachers, and the absence of Wi-Fi in schools which limits access to learning resources on the internet.